In Vivo Toxicity Evaluation of PEGylated CuInS2/ZnS Quantum Dots in BALB/c Mice - Zou, Wenyi; Li, Li; Chen, Yajing; Chen, Tingting; Yang, Zhiwen; Wang, Jie; Liu, Dongmeng; Lin, Guimiao; Wang, Xiaomei (Frontiers in Pharmacology, 2019)
.In recent years, quantum dots (QDs) have emerged as a potential contrast agent for bioimaging due to their bright luminescence and excellent photostability. However, the wide use of QDs in vivo has been limited due to underlying toxicity caused by leakage of heavy metals. Although non-cadmium QDs have been developed to resolve this issue, a comprehensive understanding of the toxicity of these newly developed QDs remains elusive. In this study, we administered PEGylated copper indium sulfide/zinc sulfide (CuInS2/ZnS), which are typical non-cadmium QDs, and analyzed the long-term effects of these nanoparticles in BALB/c mice. Body weight, hematology, blood biochemistry, organ histology and biodistribution were examined at different time points. We found no significant difference in body weight after injection of CuInS2/ZnS QDs. These CuInS2/ZnS QDs entered and were accumulated in major organs for 90 days post-injection. The majority of biochemical indicators were not significantly different between the QDs-treated group and the control group. In addition, no significant histopathological abnormalities were observed in the treated mice compared with the control mice. CuInS2/ZnS QDs did not lead to observable toxicity in vivo following either the administration of a high or low dose. Our research not only provides direct evidence of the bio-safety of CuInS2/ZnS QDs, but also a feasible method for evaluating nanoparticle toxicity.